Synthesis, Characterization and Molecular Docking of Bis-(1-(2,4-dichlorobenzoyl)-3-methylthiourea) Iron (III) Complex as Anticancer Candidate - Ruswanto Ruswanto; Feri Sandria; Winda Trisna Wulandari; Richa Mardianingrum (Jurnal Kimia Sains dan Aplikasi, 2024)
The Bis-(1-(2,4-dichlorobenzoyl)-3-methylthiourea) iron (III) complex has been synthesized from the reaction between 1-(2,4-dichlorobenzoyl)-3-methylthiourea and Fe (III) metal ion by reflux method with ethanol solvent at a temperature of 75°C for 7 hours. It was characterized by a hot stage microscope (HSM), UV-Vis, FT-IR, and mass spectroscopy. The % yield of the synthesis result was 97.58%. From the docking study on the ribonucleotide reductase enzyme, the binding affinity value was -7.76 kcal/mol, and the inhibition constant was 2.11 mM. The Bis-(1-(2,4-dichlorobenzoyl)-3 methylthiourea) iron (III) complex compounds can be synthesized and predicted as anticancer candidates.